morphological stages of the residential development and development (Journal of Planner and Development, 2011)
The neighbourhood unit is a small local community in a city dwelled by certain number of dwellers who are characterized by common features, mostly economic. They daily deal with each other & unified with the feeling of neighbourhood. The daily primary services are available in this small community (like education, shopping & entertainment). This community is separated from other communities by physical boundaries like streets, gardens… etc. The neighbourhood is not an exotic notion on human community but it is as ancient as history itself since it was there in ancient communities that dwelled on earth. Complications of urban life needs, caused by cities’ expansion, and the weakness of social relationships, imposed physical style or organization that meet those needs and keep up social relationships between dwellers at the same time. Therefore, the neighbourhood will not take its final form unless it goes through certain morphological phases. That is why this research shed the light on the morphological phases that the neighbourhood past through by taking the changes which took place in the urban environment of neighbourhood. Those changes were caused by the changing of circulation systems, construction streets that passed through the traditional urban fabric of the area under the turnover of planning priorities from fulfilling human needs, which are the basis of Islamic Arabic city planning, to fulfill machine needs which become dominant in the contemporary planning thought, and finally the change in land use in the area. This change also affected the house which is the primary unit in neighbourhood fabric.